The study of filtration on oil & gas applications / Zulkifli Baba and Azizul Ariffin - Baba, Zulkifli; Ariffin, Azizul (2004)
This project work report, the mean study type and application of Filter / Separator using for Oil & Gas and Petrochemical Industry. This report will be show how the filter / separator work and why is it very important to the petrochemical industry.